MYALGIC ENCEPHALOMYELITIS/CHRONIC FATIGUE SYNDROME (ME/CFS) SYMPTOMS IN UNDERGRADUATE AND GRADUATE STUDENTS IN MEXICO - Coffin Cabrera, Norma; Guarneros Reyes, Esperanza; Negrete Rodríguez, Oscar Iván; Miralrio Medina, Constanza; Silva Rodríguez, Arturo (Revista Electrónica de Psicología Iztacala, 2023)
Health professionals face illnesses for which is necessary to build instruments that allow diagnosis and develop treatments. One of these is Myalgic Encephalomyelitis/Chronic Fatigue Syndrome (ME/CFS). Bathia et al. (2020), state that the use of inconsistent ME and CFS case definitions has the potential to mask important population differences in access to specialist care and culturally-specific disease stigmatization. In addition, the lack agreement on a unified case definition leads to challenges in precisely describing the impairment and symptomatic presentation of the condition, and that given the afore mentioned issues with sampling heterogeneity; thus, there is a need to compare ME/CFS functional impairment and symptomatology in different countries using a consistent case definition. In Mexico, different efforts have been carried to study this Syndrome. However, prevalence data are not consistent. The goal for this study is to know relationship among frequency and severity with major symptoms for ME/CFS. Participants, undergraduate and graduate students (N=81), agreed to participate. Data will be based on a short version of the CFS Questionnaire from De Paul University, already validated for Mexican population, by Redcap platform. This questionnaire, containing 14 items and two variables of interest (frequency and severity, containing five response indicators for each item), will be published by Facebook and the main virtual media of the University we belong. Translation has been made. Preliminary results show interesting relations between age and insomnia (Factor R 0.319); weight and severity of fatigue (Factor R 0.394); frequency of pain and fatigue (Value “P” Kruskall Wallis: 0.045), correlations with factor scholar background; frequency of fatigue with minimal exercise (Value“P” Kruskall Wallis: 0.014; p = 0.05), among others. These preliminary results are promising in terms of people far away from Mexico City, can answer this questionnaire online, so we can have more accurate data concerning to prevalence of ME/CFS in this country.